26 cOllagen v, small leucine rich proteoglycans (SLRP) and surgical scar: is there a correlation?. (13th October 2015) - Akhtar, MA; Robinson, CM; Keating, JF; Salter, DM; Simpson, H
Abstract : 13 patients (11 male and 2 females) were studied to assess the relationship between surgical scars following open shoulder stabilisation or primary ACL reconstruction and the expression of collagen V, decorin and Biglycan in skin. The grading of stain on immunohistochemistry was done on a 0–4 scale. Surgical scar was scored on 1–3 scale by 2 observers. Laxity was assessed by Beighton score (0–9). 3 patients had poor cosmetic scars with a picture score of 3 (Group A). The mean Beighton score was 2.3. The mean scar satisfaction was 6.3 (0–10) on visual analogue scale (VAS). The mean scar age was 13.7 week (10–20). All were male and the mean age was 20 years (17–22). The mean decorin expression in skin was 3.6 for both superficial and deep dermis. The mean Collagen V expression was 1.3 for skin dermal papillae, Skin appendages, superficial and deep dermis. The mean Biglycan expression was 2 for skin epidermis, 3 for skin appendages, 2 for superficial skin dermis and 0.6 for skin deep dermis. 7 patients had good cosmetic scars with a picture score of 1 (Group B). The mean Beighton score was 3 (0–7). The mean scar satisfaction was 5.8 (4–8). The mean scar age was 9 weeks (3–22). There were 5 male and 2 females. The mean age was 28 (23–43). The mean decorin expression in skin was 3.3 for both superficial and deep dermis. The mean collagen V expression was 2.4 for skin dermal papillae, 2.1 for Skin appendages, 1.7 for superficial and deep skin dermis. The mean Biglycan expression was 2.3 for skin epidermis, 2.5 for skin appendages, 2.1 for superficial skin dermis and 1.1 for skin deep dermis. There was no difference in the ligamentous laxity between the 2 groups. Collagen V expression was higher in skin dermal papillae 2.4 vs 1.3 (p = 0.02) and skin appendages 2.1 vs 1.3 (p = 0.05) and Biglycan expression was higher in skin deep dermis 1.1 vs 0.6 (p = 0.1) of good cosmetic scars. This study indicates that higher skin content of Collagen V is associated with better cosmetic scars